2006
DOI: 10.1093/her/cym012
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to adoption of evidence-based perinatal care in Latin American hospitals: a qualitative study

Abstract: Selective episiotomy and the active management of labor have been shown by numerous studies to benefit women's experience of labor as well as its outcomes. However, many Latin American public hospitals have not updated their clinical practices to reflect these findings. Limited access to new knowledge, limited time and physical resources and attitudes resistant to change are factors limiting the adoption of new practices in such hospitals. Interviews were conducted with three department heads, and focus groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 14 publications
9
81
0
7
Order By: Relevance
“…The lack of adequate resources and physical facilities for EBP are universal and our finding is consistent with previous research [7,8,17,21,24,26]. In a qualitative study in Latin American hospitals, professional informants reported scarce physical facilities as their main hurdle to change perinatal care practice [21].…”
Section: Organizational/system-based Barriers To Ebpsupporting
confidence: 90%
See 2 more Smart Citations
“…The lack of adequate resources and physical facilities for EBP are universal and our finding is consistent with previous research [7,8,17,21,24,26]. In a qualitative study in Latin American hospitals, professional informants reported scarce physical facilities as their main hurdle to change perinatal care practice [21].…”
Section: Organizational/system-based Barriers To Ebpsupporting
confidence: 90%
“…While these barriers are obstructive to EBP and can negatively affect staff morale and motivation. Perhaps, the barriers could be due to communication problems [21] between staffs and managers, administrators' are unaware of their responsibilities or lack EBP knowledge. Findings from a systematic review highlighted that poor institutional support hinders the uptake of EBP [17].…”
Section: Organizational/system-based Barriers To Ebpmentioning
confidence: 99%
See 1 more Smart Citation
“…Witches are fits with previous studies in other countries. [53][54][55][56][57] Thus, the results of the present study and similar results obtained from other studies showed that the following cases were inevitable: providing appropriate facilities for implementation of EBM, providing enough time to study, performance based on evidences through workload reduction, increasing human resources, training time management and so on, teaching research method and planning, conducting and using research results, and also training the principles and standards of EBM and establishing legal, political and administrative infrastructures to provide the possibility of making changes and applying research results by health service providers, albeit, with professional, ethical and legal supervision and incentives to increase physicians' cooperation in the field of EBM, and holding courses in order to enhance health providers' ability and English The results indicated Iranian health providers have relatively low awareness of specific terms of EBM (44.2%). The lowest familiarity and understanding were of CI, level of evidence, meta-analysis and OR respectively that matches greatly with results of previous researches.…”
Section: Tabriz and Tehranmentioning
confidence: 99%
“…La propia formación médica intervencionista donde la preparación en la atención básica o de nivel I no es la adecuada o suficiente. Las instituciones de la salud que prestan estos servicios tienen escasez de personal profesional capacitado, de materiales necesarios, e instalaciones físicas no adecuadas para atender a la población adolescente embarazada (32).…”
Section: Discussionunclassified